Self-Controlled Feedback Facilitates Motor Learning in Both High and Low Activity Individuals - Fairbrother, Jeffrey T.; Laughlin, David D.; Nguyen, Timothy V. (Frontiers in Psychology, 2012)
The purpose of this study was to determine if high and low activity individuals differed in terms of the effects of self-controlled feedback on the performance and learning of a movement skill. The task consisted of a blindfolded beanbag toss using the non-preferred arm. Participants were pre-screened according to their physical activity level using the International Physical Activity Questionnaire. An equal number of high activity (HA) and low activity (LA) participants were assigned to self-control (SC) and yoked (YK) feedback conditions, creating four groups: Self-Control High Activity (SC-HA); Self-Control Low Activity (SC-LA); Yoked High Activity (YK-HA); and Yoked Low Activity (YK-LA). SC condition participants were provided feedback whenever they requested it, while YK condition participants received feedback according to a schedule created by their SC counterpart. Results indicated that the SC condition was more accurate than the YK condition during acquisition and transfer phases, and the HA condition was more accurate than the LA condition during all phases of the experiment. A post-training questionnaire indicated that participants in the SC condition asked for feedback mostly after what they perceived to be “good” trials; those in the YK condition indicated that they would have preferred to receive feedback after “good” trials. This study provided further support for the advantages of self-controlled feedback when learning motor skills, additionally showing benefits for both active and less active individuals. The results suggested that the provision of self-controlled feedback to less active learners may be a potential avenue to teaching motor skills necessary to engage in greater amounts of physical activity.